HUMAN RESOURCE ACCOUNTING AND FINANCIAL PERFORMANCE OF QUOTED DEPOSIT MONEY BANKS - CECILIA ADURAYEMI ADU; TEMITOPE VICTOR OLOMOLA (International Studies Journal)
The paper examined the effect of human resource accounting) and on the financial performance of Deposit Money Banks (DMBs)in Nigeria. Other objectives of the study were to determine the influence of HRA on capital employed and to appraise the influence of HRA on return on capital employed. Secondary source of data was adopted for this study and ten quoted deposit money banks were selected through random sampling technique while the data were analyzed using regression analytical method. It was found out that salaries and wages, training, health and safety had significant positive influence on capital employed of deposit money banks in Nigeria and salaries and wages, training, health and safety had significant positive influence on return on capital employed. This study therefore concluded that human resource accounting improved financial performance of deposit money banks. The study suggested for the management of deposit money banks to improve the general welfare of their employees through improved salaries and wages, better training and enhanced health and safety in order to improve their financial performance.